Andaman and Nicobar Administration Seventh Five Year Plan (1985-90) Draft Annual Plan Proposal for 1989-90 Volume-II (Details of Schemes) - Planning Commission (Planning Commission, 1990)
Area available in this territory fox elevation of paddy is limited and it is targeted to maximize the production of r ice by bringing more area under H.Y.V and double cropping of paddy during seventh Five Year Plan, the Physical target and programme under the Scheme are as under Supply of H.Y.V. and other improved varieties of Seed paddy to the cultivators at 20 cost subsidy and 1007 subsidy on transport. To maximize the production of paddy by bringing more cultivable land under H.Y.V. and double cropping in this Territory.
Andaman and Nicobar Administration
Andaman And Nicobar Administration
Keywords: Secretariat Economic Services; Monitoring Plan Implementation; Strengthening of Diet Planning Machinery; Rehabilitation; Government Press; Public Works; Official Language; Intensive and Multiple Cropping Programme; Demonstration in Cultivators Field; Improvement in distribution of Agricultural Inputs; Development of Spices and Cashew cultivation in Tribal -Area